Pembelajaran Akidah Akhlak Dalam Menumbuhkan Sikap Tawadhu’ Siswa di MTs Ma’arif Pucang, Secang, Magelang - Muhammad Faqih Falah; Nasokah Nasokah; Sofan Rizqi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This thesis aims to: 1) To find out the concept of Aqidah Akhlak learning in cultivating an attitude of tawadhu' in students at MTs Ma'arif Pucang, Secang, Magelang; 2) To find out the implementation of Aqidah Akhlak learning in cultivating an attitude of tawadhu' in students at MTs Ma'arif Pucang, Secang, Magelang.This thesis uses a research approach using qualitative field research, Qualitative field research itself is research that has characteristics, which basically states the true situation or as it is without changing it into symbols or numbers.The results of the research show that: 1) the concept of learning moral beliefs in cultivating students' attitude of tawadhu' is very appropriate to be implemented in an educational institution, especially at MTs; 2) implementation of moral aqidah learning in cultivating students' attitude of tawadhu' which has been implemented optimally even though each student has different thinking abilities; 3) supporting and inhibiting factors in learning moral beliefs in cultivating students' attitude of tawadhu'. Keywords : Learning, Moral Creeds, Students' Tawadhu' Attitude.